A formal foundation for transformations in model driven engineering - Giandini, Roxana Silvia (2008)
In the MDE (Model Driven Engineering) paradigm, models are thought to be the primary conductors in all software development aspects. A PIM (Platform Independent Model) is transformed into one or more PSMs (Platform Specific Model); hence, a specific PSM is generated for each specific technological platform. In turn these output models may be transformed into another set of models until finally the output consists of program code that can be executed. Model transformation is the MDE engine; models are no longer mere contemplative entities and become productive entities. The MDE initiative covers a broad spectrum of research areas: modeling languages, definition of languages for model transformation, construction of support tools for the different tasks involved, application of concepts to development methods and specific domains, etc. Currently, some of these aspects are well-based, and are being applied with some success; however, other aspects are still undergoing their definition process. In this context, it is necessary to make every effort to convert MDE and its concepts and related techniques into a coherent proposal, based on open standards, and supported by mature tools and techniques. Model transformations require specific languages for their definition; these languages should have a formal base, for example, a metamodel that supports them and allows for an automated treatment.